Coenzyme Q-10: a potential role in alleviating long Covid-19 symptoms - Juwalita Surapsari (World Nutrition Journal, 2022)
Globally, as of mid August 2021 there have been more than 200 million confirmed cases of COVID-19 reported to WHO. About 80% of COVID-19 cases are asymptomatic and mild, and most of the cases resolved within 2-4 weeks. While severe pneumonia and critical multi-organ failure occurs in 15% and 5% respectively, and can last for 3-6 weeks. The post-COVID symptoms, initially referred to as ‘long COVID’ or ‘long-haul COVID’, are now collectively referred to as ‘post-acute sequelae of SARS-CoV-2 infection” (PASC).